Embedding Carbon Nitride into a Covalent Organic Framework with Enhanced Photocatalysis Performance. Issue 13 (8th June 2018) - Pan, Junquan; Guo, Liping; Zhang, Siquan; Wang, Ning; Jin, Shangbin; Tan, Bien
Abstract: We report a new strategy to construct porous carbon nitride (PCN) by embedding a heptazine unit–the primary building block of carbon nitride–into the backbone of a covalent organic framework (COF). The strategy results in a new type of PCN which bears a fibrous morphology, high surface area and wide visible absorption. The photocatalytic performance was evaluated by photodegradation of an organic dye. We found that the introduction of the heptazine unit has a prominent effect on the catalytic activity, which demonstrates an effective strategy to prepare carbon nitride materials. This work opens up a new way for the preparation of carbon nitride for photocatalysis applications. Abstract : Covalent organic frameworks (COFs) are a type of crystalline materials with tunable structures. Here COFs are presented as a powerful platform to introduce carbon nitride structures to create a new type of porous carbon nitride (PCN) material with high surface area, wide visible absorption and fibrous morphology. These advantages endow the PCN with enhanced photocatalytic performance and thus providing a new strategy to synthesize carbon nitride for photocatalysis.